Public procurement's place in the world : the charge towards sustainability and innovation - Decarolis, Francesco; Frey, Marco; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This volume addresses different issues related to green innovation procurement as well as exploring the challenges involved in public procurement. It offers a broad array of perspectives, addressing both general, abstract problems of optimal public procurement and concrete cases of national or even local public procurement systems.
Keywords: Government purchasing; Comparative government